Different understandings of the notion of victim and their consequences on the social attitude towards victimization - Nikolić-Ristanović Vesna (Temida, 2012)
This paper analyzes different understandings of the notion of victim primarily from the point of view of their inclusion of different forms of victimization. The political influence and the impact of prejudices and stereotypes on both determination of the notion and the society’s attitude toward victims are pointed out as well. The notion of victim and its consequences on the rights of victims are explored in the context of theoretical concepts of „ideal victim“, „real victim“, „innocent“ or a victim who deserves help. In the conclusion of the paper, the proposal for a comprehensive and inclusive concept of victim, which would include all persons who were in any manner violated or threatened by crime, war or other forms of violations of human rights as well as natural disasters, is presented.